2018
DOI: 10.1080/09540261.2019.1566116
|View full text |Cite
|
Sign up to set email alerts
|

How competent are non-specialists trained to integrate mental health services in primary care? Global health perspectives from Uganda, Liberia, and Nepal

Abstract: Evaluations to objectively assess minimum competency are not routinely implemented for training and supervision in global mental health. Addressing this gap in competency assessment is crucial for safe and effective mental health service integration in primary care. To explore competency, we describe a training and supervision program for 206 health workers in Uganda, Liberia, and Nepal in humanitarian settings impacted by political violence, Ebola, and natural disasters. Health workers were trained in the Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 38 publications
2
63
0
Order By: Relevance
“…Furthermore, as mounting evidence from HICs shows that common therapeutic factors play a significant role in therapeutic outcome (Lambert and Kleinstauber 2016), competence in these is particularly important to consider when training non-professionals in LMICs. An 18-item tool to measure lay counsellor competence in common factors when delivering interventions in LMICs has been developed and recently evaluated (Kohrt et al 2015;Kohrt et al 2019). For researchers conducting future trials, measurement and reporting of therapist competence and use of common factors through such tools, and direct observations of sessions, would provide valuable information.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Furthermore, as mounting evidence from HICs shows that common therapeutic factors play a significant role in therapeutic outcome (Lambert and Kleinstauber 2016), competence in these is particularly important to consider when training non-professionals in LMICs. An 18-item tool to measure lay counsellor competence in common factors when delivering interventions in LMICs has been developed and recently evaluated (Kohrt et al 2015;Kohrt et al 2019). For researchers conducting future trials, measurement and reporting of therapist competence and use of common factors through such tools, and direct observations of sessions, would provide valuable information.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…In the aftermath of the 2015 earthquake of 7.8 magnitude, many high profile mental health projects emerged within rural Nepal only to witness a discrepancy between supply and demand [36]. For example, in 2008 the WHO initiated mhGAP in Nepal [45], and between 2012 and 2019, the UK Aid Direct and Department for International Development sponsored the Programme for Improving Mental Healthcare (PRIME), a project which scaled up mental health services by integrating it with primary care. Unfortunately, integration proved difficult and later analyses of both mhGAP and PRIME revealed that local understandings of mental illness and high levels of stigma precluded community awareness, demand, and access to basic mental health services [46,47].…”
Section: Settingmentioning
confidence: 99%
“…The CPSW training includes an overview of psychosocial concepts, cause and effects of psychosocial issues, basic communication skills, common mental health problems in communities, group facilitation skills, and psychoeducation. Competency is evaluated before and after the CPSW training with a standardized role play assessment tool (ENACT) that has been developed in Nepal and used for non-specialists in humanitarian settings [20].…”
Section: Study Arms Group Pm+ Interventionmentioning
confidence: 99%